A Comparison of Global Timber Models - 김윤형 (한국농촌경제연구원, 2011)
This study identifies differences of global timber models in its three different versions by comparing marginal abatement cost. The forest-only model has a relatively linear marginal cost curve; the other two models show concave cost curves, indicating that the marginal cost for carbon sequestration increases faster than in the forest-only model. Such basic differences among the models may be caused by the characteristics of the CET(Constant Elasticity of Transformation) model. The differences between the forest-only model and CET model are more narrowed when CET results are converted to physical units. This study contributes to the enhancement of the understanding of GTM development and provides foundation for future studies to improve global timber modeling.
Keywords: global timber model; constant elasticity of transformation; carbon sequestration cost; global timber model; constant elasticity of transformation; carbon sequestration cost